TRANSFORMASI STRUKTUR PEREKONOMIAN DAN KESEJAHTERAAN MASYARAKAT PEDESAAN - Abbas Affandi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1997)
There are three points to discuss in this paper. The first is to observe influences of economic-structures transformation on rural society's prosperity. The second is to analyze impacts of production factors transformation on traditional economic agents. The third is to scrutinize institutional factors role on prosperity of rural economic structures. In this paper, rural economic structures can be classified into three groups. They are agricultural, non-agricultural and combination of the two. The result shows that (1) transformation of economic structure has positive impact onfamily's prosperity in rural area. The non agricultural activities tend to stimulate the creation of the prosperity of rural society than the agricultural ones do. (2) Capital and education are very determining factors to improve rural society's prosperity. In the structures of economic combination and non-agricultural, technology also has significant role in increasing society's prosperity. On institutional role, it is known that KUD (Village Unit Cooperation) in its manifestation has not functioned wellas to increase farmers' prosperity.